2023
DOI: 10.32604/csse.2023.034085
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Interactive Videos Empowered the Experience of Learning Management System

Abstract: The Learning management system (LMS) is now being used for uploading educational content in both distance and blended setups. LMS platform has two types of users: the educators who upload the content, and the students who have to access the content. The students, usually rely on text notes or books and video tutorials while their exams are conducted with formal methods. Formal assessments and examination criteria are ineffective with restricted learning space which makes the student tend only to read the educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The first research question investigated the perceived value of interactive videos in improving learners' listening comprehension and motivation to listen in English. Globally considered, the data indicated that interactive videos kept learners engaged, which lent support to Akram et al (2023). Moreover, watching interactive videos with embedded components not only increased their motivation but also improved their performance.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The first research question investigated the perceived value of interactive videos in improving learners' listening comprehension and motivation to listen in English. Globally considered, the data indicated that interactive videos kept learners engaged, which lent support to Akram et al (2023). Moreover, watching interactive videos with embedded components not only increased their motivation but also improved their performance.…”
Section: Discussionmentioning
confidence: 72%
“…Graham, 2016), but also for making interactive videos a potentially appropriate tool for formative assessment in language instruction (Kolås, 2015;Smithwick et al, 2018). Moreover, as Akram et al (2023) stress, interactive lectures in the form of annotated (interactive) videos can increase user engagement.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Kolås emphasized its benefits in motivating students and improving their attitudes towards learning [21]. Baker adds that student engagement is enhanced when they have control over the navigation of learning materials [22], and the ability of interactive video to provide immediate feedback and allow skill practice at an individual pace is emphasized as one of its advantages [23]. Clark & Mayer support using interactive videos in online education for self-directed learning [24], and Merkt & Schwan examine how these videos support the flipped learning model [25].…”
Section: Use Of Interactive Videomentioning
confidence: 99%